Criminal Law Politics: Law Concerning Corruption Crimes Eradication - Yazid Bustomi; Reza Pahlevi; Ariyanti Lady Sakinata (UNIFIKASI : Jurnal Ilmu Hukum, 2021)
The purpose of this study is to analyze the law authority through criminal law politics states in the law concerning corruption. This study employed a normative juridical method with conceptual and statue approaches. This research collected the data from primary and secondary legal materials. These are to obtain a critical study of legal issues happening in society. The findings revealed that the criminal act of corruption does not provide a deterrent effect and is actually detrimental to the state. In addition, this study also found that the law concerning corruption increases the state’s burden. This is because the prison sentence for corruptors is too light. The amount of money proceeds from corruption is not comparable to state spending in supporting the life of corrupt convicts in prison. The standard of penalty state in the law is too light compare to the result of corruption. Thus, it is necessary to reform the law on corruption due to the absence of proportionality in law and large losses to the state when dealing with corruption. The highest standard penalty for corruption only amounts to one billion Rupiah. In fact, many corruption cases reach to tens billions and even trillions rupiahs.